Selection and validation of reference genes for quantitative real-time PCR analysis of gene expression in Cichorium intybus - Delporte, Marianne; Legrand, Guillaume; Hilbert, Jean-Louis; Gagneul, David (Frontiers in Plant Science, 2015)
Plant polyphenols represent a huge reservoir of bioactive compounds. Industrial chicory, an important crop from northwestern Europe, accumulates an original combination of such compounds i.e. chlorogenic, isochlorogenic, caftaric and chicoric acids arising from the phenylpropanoid pathway. For a complete understanding of these biochemical pathways, analyses of gene expression using quantitative real-time PCR (qRT-PCR) should be considered. Because cell cultures are a model of choice for secondary metabolism investigations, this study described for the first time the validation of reference genes for this system in chicory. Eighteen potential reference genes were obtained by mining expressed sequence tag databases of chicory for orthologs of Arabidopsis thaliana genes currently used as reference genes. Twelve genes passed the qRT-PCR standard requirements and their expression stability across different samples was tested using three distinct softwares: geNorm, NormFinder and BestKeeper. In cell cultures grown under various conditions, TIP41 (TIP41 like protein) was shown to be the most stable gene. Further validation of the proposed reference genes was done by normalization of expression levels of a group of genes of interest. In order to assess the potentiality of the proposed list of candidate reference genes, theses genes were in parallel tested on another experimental design i.e. chicory seedlings. In this case, the best reference gene identified was Clath (Clathrin adaptator complex subunit). The results highlight the importance of the use of properly validated reference genes to achieve relevant interpretation of qRT-PCR analyses. Here, we provide a list of reference genes suitable for future gene expression studies in chicory.